Climate-Sensitive Mining : Case Studies - Sekar, Sri; Lundin, Kyle; Tucker, Christopher; Figueiredo, Joe; Tordo, Silvana; Aguilar, Javier (World Bank, Washington, DC, 2019)
The mining industry, which provides input to almost every product and service in the world, is a critical component of sustainable growth in mineral-rich countries and the economy at large. This report is intended to deliver an account of mining technologies, processes, and strategies that seek to incorporate environmental sustainability considerations and have the potential for local value creation and green growth. The analysis focuses on three areas--renewable energy, water management, and automation and transportation--that are considered to have the broadest impact on environmental sustainability and in-country value creation through economic linkages. A reference case study is presented for each of the four benchmark minerals: gold mining in Burkina Faso, iron ore in Australia, copper in Peru, and cement in India. The report is part of a series of background reports that inform the research on Building Resilience: A Green Growth Framework for Mobilizing Mining Investment.